HISTORICAL AND CULTURAL SPACE AND FORMATION OF COMMUNICATION COMPETENCIES - Mamadjonova Shakhlo Shukurjonova (Western European Studies, 2024)
The article considers communicative culture occupies a leading place in the general cultural and professional development of a personality and, of course, is one of the priority tasks of education, is considered as a special object of modeling pedagogical systems in the unity of their structural and functional components and is presented as the most important component of humanitarian education.
Keywords: history; culture; space